Evaluation of Common Beliefs and Practices of the Slaughterhouse Butchers Tamale Metropolis Ghana - Asare, Solomon Ossom; Omanchi, Emmanuel Olofu; Shehu, Amina Jummai; Tahidu, Issifu; Konka, Dadaniel (Darul Yasin Al Sys, 2025)
Meat quality and butcher’s awareness plays a key role in production of hygienic meat and preserving the public health. A structured questionnaire was developed and a total of 150 butcher were surveyed in the pilot study. The aim was to evaluation the common beliefs and practices of the slaughterhouse butchers. The survey revealed that 54.5% of the butchers a family business and does not require any formal training and has No need for registration to work as a butcher. And about 62.6 % Use local implements in the slaughter of animal. With about 58.8 % has the knowledge of protective materials during operation, however, 53.8% practice skinning of animals with local knife and bare hands. Based on the results obtained in the study, it is concluded that most of the butchers required education and awareness training about hygienic meat production, threatful meat borne diseases, sanitary conditions and hygienic slaughter techniques in the butcher shops to safe guard the health of themselves and meat consumers.